A new decision model for economic evaluation of novel therapies for HCV - Ruggeri, Matteo; Cicchetti, Americo; Coretti, Silvia; Cammà, Carlo; Caporaso, Nicola; Gasbarrini, Antonio (Farmeconomia. Health Economics and Therapeutic Pathways, 2014)
In 2014, the European Medicines Agency (EMA) has given the license to two new direct-acting antiviral: sofosbuvir and simeprevir. The evidence provided by the studies, reported a high rate of SVR even in patients with decompensated cirrhosis. This and other innovative elements are potentially adept at changing the entire natural course of HCV. However, the dramatic prevalence rates of HCV observed in Italy, and the high prices that are expected to be required by the pharmaceutical industry, raises some critical issues about how to regulate access to such drugs. The objective of this article is to present a new decision model for the evaluation of novel therapies for HCV. This model is intended to provide a tool for the decision-maker that seeks to address the main issues related to the introduction of HCV new treatments. The model that we have structured follows the classic Bayesian approach, using data from reference literature for staging the action of treatments depending on the level of fibrosis (F0, F1, F2, F3, F4). The model is designed to consider patients with all genotypes and allows to make comparisons between innovative and traditional therapies (dual, triple, IFN free, PI combinations, etc.), for both experienced and naïve patients. In addition, the model is used to simulate mixed cohorts of patients, representing a population with HCV with different levels of fibrosis and different genotypes. To show the potential of the model, we created some simple scenarios assuming different levels of SVR and pricing. The results of our model show that, even assuming an SVR rate of 100%, the administration of new treatments for HCV subjects F1 / 2 has an incremental cost-effectiveness ratio not sustainable. In contrast, for the subjects F3 and F4, low incremental SVR rates and an incremental cost of the innovative therapy of € 40,000 would be cost effective. The added value of this model is its versatility and applicability to diverse assessment needs. In addition, the model offers an opportunity for reflection even to the industry, which in the years to come will have to develop strategies for entering the market and offer sustainable prices for decision-makers and at the same time remunerate the investment in research and development consistently with the expectations of the shareholders.